PEMETAAN TINGKAT BAHAYA ANGIN PUTING BELIUNG BERBASIS SISTEM INFORMASI GEOGRAFIS DAN PENGINDERAAN JAUH DI KABUPATEN BANDUNG BAGIAN TIMUR - Destiana, Mutia; Setiawan, Iwan; Murtianto, Hendro; Somantri, Lili (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Every year, Bandung Regency often sustains windstorms and strong winds. Based on previous research, the disaster events formed a clustered pattern around the south of the Saguling Reservoir to the northwest-north, some of which were found in East Bandung Regency. Over the last 10 years, the eastern part of Bandung Regency has been hit by 72 windstorms. Causing people injuries, suffering, displacement, and damage property. The main objective of this study is to determine and analyze the level of windstorm hazards and identify the level of affected area from windstorm hazard in the eastern part of Bandung Regency. This research as a whole uses the Geographic Information System method in the form of overlays, weighting, and scoring, as well as remote sensing methods which are used as data providers - data parameters for the level of windstorm hazard including data on a slope, surface temperature and land cover. The results showed that East Bandung Regency had a low to high hazard level with a moderate hazard level being the widest hazard level of 407.72 km2 followed by the second widest class, namely a high hazard level of 317.42 km2 and a low hazard class of 33.27 km2. The distribution of affected area from windstrom hazard resulted in 9 classification classes with the classification being the first order to be considered namely the level of population density and the level of danger (high,high). There are two sub-district with the with the classification (high,high) are Cileunyi District and Majalaya District.